Technology Transfer Office - Helmi, Mohamed Isa (Penerbit UMP, 2012)
Commercialization of technology is a collaborative process between the Technology Transfer Office, researchers and partners. Therefore, Universiti Malaysia Pa hang (UMP) now has an Office of Technology Transfer (TTO) under the Department of Research & Innovation dedicated to identifying research which has potential commercial interest as well as strategies on how to exploit it. For instance, a research outcome may be of scientific and commercial interest, but patents for the findings are issued for practical processes, and so, a person - who need not necessarily be the researcher - must come up with a specific practical process, proof of concept and market prototype.